The Western Borderlands of the United States and Mexico – History not Forgotten. Issue 2 (2nd April 2020) - Howe, Mark L.
Abstract : The United States – Mexico War (1846–1848) and the division of the two countries by both land and water boundaries changed the border landscape. One change was the establishment of International Boundary Monuments. These extend from the Rio Grande river in El Paso, Texas to the Pacific Ocean, marked first with rock piles, but later replaced with permanent obelisks. Today many original monuments are mistaken for rocks or graves and not the history they truly convey. The old Spanish trade route of the Camino Real from Mexico City to Santa Fe, later developed at El Paso into a smelter when the railroad arrived. With the railroad and the smelter came people who settled into what was called Smeltertown. This paper examines the forgotten boundary monuments and Smeltertown artifacts of the El Paso – Ciudad Juarez nexus and the focus of historic archeology along the border and what is still here.